Combined materials characterization by area detector investigations using hard X-rays. Issue 1 (April 2015) - Brokmeier, H-G; Maawad, E; Bolmaro, R E; Zhong, Z Y; Schell, N
Abstract: Materials characterization includes a long list of information's which are on one hand important for process optimizations and on the other hand key knowledge for application, lifetime and failure predictions. With the help of area detector investigations one is able to get simultaneously all information related to line position, line intensity and line broadening of Bragg reflections. Examples are residual stress profiles, quantitative texture mapping, diffraction elastic constants, lattice dependent stress-strain curves, thermal expansion coefficients and defect densities. A very special case is high energetic synchrotron radiation which allows very fast and complete detection of generalized pole figures, namely intensity pole figures (texture), line broadening pole figures (micro-strain) and line position pole figures (macro-strain) using complete Debye-Scherrer rings.